2020
DOI: 10.1186/s12957-020-01944-2
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term outcomes of surgery for colorectal and non-colorectal liver metastasis: a report from a single center in the Baltic country

Abstract: Background: The liver is a major target organ for metastases of various types of cancers. Surgery is a wellestablished option for colorectal liver metastases (CRLM). Regarding the improved surgical and anesthetic techniques, the safety of liver resection has increased. Consequently, the interest in the surgical management of non-colorectal liver metastases (non-CRLM) has gained significant attention. Therefore, this study was designed to investigate the surgical treatment outcomes for non-CRLM and to compare i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In the last decades, liver surgery has dramatically developed, becoming a standardized and safe operation with perioperative mortality rates 1.0% and 2.0% even for advanced laparoscopic and open liver resections, respectively 1 . Improvements in preoperative evaluation, patient selection, advances in surgical technique and technology are the main reasons of this enhancement 2,3 . The cornerstone for a successful oncologic liver surgery relies on obtaining a R0 resection margin and preserving a proper healthy liver parenchyma to achieve better short- and long- term outcomes 4,5 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decades, liver surgery has dramatically developed, becoming a standardized and safe operation with perioperative mortality rates 1.0% and 2.0% even for advanced laparoscopic and open liver resections, respectively 1 . Improvements in preoperative evaluation, patient selection, advances in surgical technique and technology are the main reasons of this enhancement 2,3 . The cornerstone for a successful oncologic liver surgery relies on obtaining a R0 resection margin and preserving a proper healthy liver parenchyma to achieve better short- and long- term outcomes 4,5 .…”
mentioning
confidence: 99%
“…1 Improvements in preoperative evaluation, patient selection, advances in surgical technique and technology are the main reasons of this enhancement. 2,3 The cornerstone for a successful oncologic liver surgery relies on obtaining a R0 resection margin and preserving a proper healthy liver parenchyma to achieve better short-and long-term outcomes. 4,5 To achieve these goals, the application of intraoperative navigation tools has been required as a part of the progressive developments in liver surgery.…”
mentioning
confidence: 99%
“…In addition, for high-risk patients, positron emission tomography computed tomography (PET-CT) and invasive procedures such as needle biopsy are also recommended for definite diagnosis if there is an undefined low-density liver lesion, because they are expensive and are not justified for general screening. If a positive liver result is found in a targeted examination, we can change the treatment plan in time so as not to delay the disease such as radiofrequency ablation and surgery [ 34 36 ]. Of course, this study only provides a reference rather than a guide, and specific decisions should be made based on clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Patients have a slightly better prognosis if they do not have metastatic disease, if they have an adenocarcinoma component within the tumor, or if they respond to chemotherapy [ 23 ]. Unlike patients with non-colorectal non-neuroendocrine liver metastases [ 24 26 ], surgery, especially in the presence of metastatic disease, may not provide any survival benefit for most patients [ 23 ]. Fields et al [ 27 ] demonstrated that the total number of positive lymph nodes was an independent predictor of survival in patients with colon NENs.…”
Section: Discussionmentioning
confidence: 99%